Formulasi Strategi Pengembangan Produk terhadap Tingkat Volume Penjualan Studi Kasus pada PT. Indomilk - Suardi, Weman (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2005)
IE matrix is derived by using the values of analysis results using IFAS and EFAS, where IE matrix is derived as follows: The position of the company in IE matrix is in the quadrant which can be described as Hold and Maintain. The total score of IFAS is 2,511 and total score of EFAS is 2,572. The position of the company in IE matrix has strategy implication called Market Penetration and Product Development. After implementing calculation it is applied into SWOT matrix. The value of the relation of product development strategy with the sales volume can be measured by using regression analysis and correlation analysis, where X is product development cost and Y is the volume of sales. Key words: Product Development Strategy; Sales Volume.